A novel process design for CO2 capture and H2S removal from the syngas using ionic liquid. (10th March 2019) - Wang, Yinglong; Liu, Xiaobin; Kraslawski, Andrzej; Gao, Jun; Cui, Peizhe
Abstract: In coal chemical industry, sour gas removal from syngas using Rectisol technology is facing the problem of large cold energy consumption. In this work, a room-temperature process for sour gas removal from syngas is proposed. Ionic liquid is used as physical solvent. The study of ionic liquids shows that [bmim][Tf2 N] is a suitable IL that can achieve the simultaneous removal of H2 S and CO2 that makes the process more simple. The process is modeled and simulated and the results show a good performance which CO2 and H2 S removal rate reaches 97.6% and 95.3%, respectively. Sensitivity analysis is carried out to study the influence of operating conditions on process performance, it provides the basic data for researchers to make decisions. Compared with the Rectisol process, the ionic liquid process has the advantage of operation at room temperature which saves large amount of energy used for refrigeration. Meanwhile, ionic liquid has low loss ration and low energy consumption in recovery. The comparison shows that ionic liquid is a good alternative to the cold methanol for CO2 capture and H2 S removal on a large scale. Highlights: A novel path for CO2 capture in coal chemical industry. CO2 capture and H2 S removal can be achieved simultaneously using ionic liquid. The process is operated at room temperature. The CO2 removal ratio of the process is up to 97.6%.